When Lawfare Becomes Warfare: Personal Stories, Political Landscapes: CODESRIA Bulletin Online, No. 4, June 2026 - Shivji, Issa G. (CODESRIA Bulletin, 2026)
When the bourgeoisie feels confident, when there is relative peace and stability, and when the class struggle is at a low ebb, bourgeois rule expresses itself through law. Law becomes the site of contestation and struggle. Lawfare has a dual character. In so-called peaceful times, the ruling class uses law in various ways to dominate and hegemonise its interests. The process has its own contradictions, creating cracks in the state’s legal armoury. These are prised open by subordinate classes, giving public expression to their interests. Thus, subordinate classes bring their grievances to the public domain. I call this insurgent lawfare. When the bourgeoisie is in crisis, when the state is fractured, when the class struggle is intense and the system feels threatened, the veneer of law is dispensed with. Lawfare becomes warfare—openly, viciously and brutally. There is no more pretence of rule of law, human rights and judicial intervention. The repressive apparatuses of the state show their true colour—force. Consensus breaks down. Coercion comes forth—naked, unmasked, shameless. Spaces for insurgent lawfare are narrowed or closed. Such is the situation internationally where the contradictions of financialised racial capitalism are concentrated in Gaza. In Tanzania, together with my colleagues, I have been involved in insurgent lawfare for over forty years. Last year in October, during the general election, I had the misfortune of witnessing the warfare. In this presentation I weave the narrative of lawfare becoming warfare through personal stories, anecdotes and memories. Low-intensity lawfare Mine was the first post-Arusha Declaration generation at University College, Dar es Salaam. The university was then one of three constituent colleges of the University of East Africa. The campus was teeming with foreign radical faculty, who included Walter Rodney. Some from the North were fascinated by the radical African ‘experiment’. Others from liberation movements and activist politics in their countries found a temporary sojourn on the campus. The student body had its share of radicals too, some of whom had flown their countries to seek exile in Tanzania. University College also attracted students from Kenya and Uganda. Among the Ugandan students was Yoweri Museveni, the future leader of the guerrilla movement against Idi Amin Dada and later Obote II. The Arusha Declaration, Tanzania’s socialist blueprint, became the harbinger of campus debates. In October 1966, university students demonstrated against compulsory national service. Nyerere was enraged. He expelled some 300 of them. It was a turning point. Here was the political elite-in-the-making that was refusing to serve the nation without being given, what Nyerere called, their ‘pound of flesh’ (Coulson 2013: 221). Expulsion of students en masse traumatised the faculty. They held a major conference to reexamine themselves and their teaching. One of the outcomes of that conference was the introduction of a compulsory, interdisciplinary common course.2 The Faculty of Law, under some young radical liberals and Marxists, introduced their own course called the ‘Social and Economic Problems of East Africa’. Sol Picciotto, a vibrant Marxist, coordinated the course (Picciotto 1986, in Shivji, 1986: 36–47). The course was wide-ranging in its scope. Picciotto exposed us to Marxist texts and other important thinkers, like Frantz Fanon, Kwame Nkrumah, C. L. R. James and others. Some students, self-identifying as revolutionaries, including me, supplemented class readings with others in our Sunday ideological classes. Ideological classes were organised by the University Students African Revolutionary Front (USARF), chaired by Yoweri Museveni (see, generally, Hirji 2010). This was the context that built and bred radical students in the Faculty of Law. Law students at the University of Dar es Salaam played a leading role in spearheading student struggles (Shivji 2021a: 210 et seq). How did we, the radical law students, see law then? We believed law was the superstructure of bourgeois society. Its purpose was to mystify social reality. Bourgeois legal ideology rationalised and justified the oppressive nature of capitalist rule. The task of radical lawyers was to unmask the ideological nature of law. The task of a lawyer-intellectual, I wrote in 1972, was: to analyse the legal forms to reveal the real substance—the exploitative economic and social and political … relationships that underlie much of law. Failing this critical role, the lawyer is likely to become an ‘intellect worker’; a technocrat in the service of ruling classes (Shivji 1972: 1–2).3 During this period, my writing was more political then legal. My long essay, Tanzania: The Silent Class Struggle (1970, 1973), and its sequel, Class Struggles in Tanzania (1975, 1976, 2025), were written as contributions to student debates on the class nature of Tanzanian socialism. While we debated class struggle, the state was busy passing a plethora of widely worded so-called developmental legislation devoid of any rights or checks and balances. The postcolonial state inherited the colonial legal armoury, replete with oppressive laws such as the Collective Punishment Ordinance, the Deportation Ordinance and a host of vagrancy laws4 (see, generally, Martin 1974). Vagrancy laws entailed sending back ‘vagrants and idlers’ in towns to their ‘home’ villages.5 These laws reflected the colonial mindset that ‘natives’ did not belong in urban areas. Their home was their village of origin. Towns and cities were the preserve of colonial administrators, immigrant communities and ‘detribalised’ Africans. The colonisers left. Their mindset remained, ingrained in the ‘detribalised’ independence elite. The 300-plus expelled students in October 1966 were sent ‘home’. When Nyerere had finished his ‘pound of flesh’ speech, his order was, ‘Go home!’ The Collective Punishment Ordinance, on the other hand, derived its rationale from colonial anthropology, which considered ‘native’ villagers too ‘primitive’ to understand individual responsibility. So, when a crime was committed in a village, such as cattle theft, the whole village was punished. As I said in my 1990 monograph, State Coercion and Freedom in Tanzania, this was ‘clearly a mechanism on the part of the colonial state to strike terror in the hearts of peasants so as to better control them’ (Shivji 1990: 29). Oppressive laws did not simply stay in the statute books. They were used as and when the state deemed them necessary. Many postcolonial laws derived their rationale from colonial laws and practices. The 1983 Human Resources Deployment Act of 1983, for example, was built on a rationale similar to colonial vagrancy laws. The Collective Punishment Ordinance continued to be deployed. In 1984, it was used against Wataturu families residing in eight named villages. They were allegedly responsible for the deaths of forty-nine persons and the theft of ‘767 heads of cattle, 30 goats, 20 sheep and 4 donkeys’. ‘The President ordered every Kitaturu family resident in the said villages to pay “such number of cattle, goats, sheep, donkeys or its equivalent in other terms as will realise 767 heads of cattle, 30 goats; 20 sheep and 4 donkeys”’ (Shivji 1990: 30). There was no trial. There was no evidence tested in courts. There were no court orders. The punishment was ordained by an executive fiat and executed by the administrative machinery. The colonial legal armoury was further replenished by the postcolonial state adding its own rightless and discretionary laws. There was a corpus of so-called developmental laws—laws that were supposed to ‘modernise’ backward pastoral and peasant communities. Under the Range Development Act of 1964, for example, ‘selected’ pastoralists were relocated to state ranches managed by expatriates with little understanding of local customs and systems. Residents were turned into a kind of employee. They detested it. They voted with their feet, returning to their homesteads. Our Law and Development lecturer, Professor Robert Seidmann, a liberal American, held up the Range Development Act as a fine piece of social engineering à la Roscoe Pound. Needless to add, the scheme was supported by USAID funding. A couple of us in the class militantly took issue with Seidmann’s position. The Rural Settlements Commission Act of 1963 was established in the same vein, to operationalise village settlement. Both schemes were an utter failure. They were abandoned at great cost (Tenga 1986, in Shivji 1986: 98–103; Shivji et al 2020, Book 3: 100–101). The post-Arusha Declaration forced villagisation was of a different genre. No law was passed to regulate it. The whole operation was mounted by the decision of the party and executed forcefully by local administrators with the help of armed militias (Shivji et al 2020, Book 3: 182–185). To be sure, Nyerere’s low-intensity lawfare was not challenged in courts. The development imperative reigned supreme. The legal fraternity largely accepted the use of law as an instrument to spearhead social change. Besides, Nyerere was a popular leader with enormous legitimacy and the goodwill of the population. What is more, in cases of extreme abuse of power particularly by the coercive apparatuses of the state, Nyerere ensured criminal liability and political accountability. In popular consciousness, therefore, abusive use of law was perceived more as an aberration than a systemic expression of the bourgeois legal system. *** Student struggles of the late 60s and early 70s on campus had their limits. The more militant and theoretically grounded among us began to agonise and interrogate our practices. Did we, petty bourgeois intellectuals, espousing the cause of workers and peasants, have real-life connection with the working people? Wasn’t our struggle patronising? Didn’t we need to move from agonising to organising? In the midst of such soul-searching, a doctrinal debate broke out on campus among those who identified themselves as Marxist-Leninists. Dani Nabudere and some of his cohort of exiles from Uganda took it upon themselves to expose those they labelled neo-Trotskyites. Nabudere wrote a number of polemical pieces against my Class Struggles in Tanzania (Tandon 1982). The so-called Dar debate split the nucleus of the Tanzanian left. To be fair, the debate did raise some fundamental questions. Unfortunately, it was so ‘scriptural’ and polemical that the so-called debate became a one-sided harangue. One of the positive outcomes of the debate was that a few Tanzanian comrades took more practical steps. One of our fine comrades, Henry Mapolu, resigned from the university and joined the Friendship Textile Mill as a Workers Education Officer. A few years later, another comrade, Abunuwasi Mwami, emulated Mapolu and joined Ubungo Farm Implements. Other comrades helped them to develop Kiswahili teaching and reading material for the education programme.6 I, who continued to be at the university, enrolled as an advocate in September 1977. Thus began my legal aid practice and my participation in the insurgent lawfare. Insurgent lawfare In this narrative of selected litigation, I interweave the story of my court cases, academic/public writings and activist work on non-legal platforms and in organisations. The narrative begins with my maiden case, goes through a couple of major cases during the transition from nationalism to neoliberalism, and ends with a controversial constitutional case on the question of the Union. I have tried to avoid technical and procedural details, except for a few juicy ones. The maiden case The year was 1979. The nation was gripped by a deadly cholera outbreak. I was browsing through legal aid files of the Tanganyika Law Society in their rickety office on Makunganya Street. One hot, humid afternoon, a haggard person walked in. Long hours of manual work had worn him down. He looked older than his age. He handed me a letter. The letter was from Chief Justice Francis Nyalali, requesting the Law Society to give the bearer and his eleven fellow labourers legal assistance. Nyalali belonged to the first generation of post-independence judges who had a soft heart for the disadvantaged. They had not yet been infected by the neoliberal virus. Witnessing my enthusiasm, the chairman of the committee assigned me the legal aid brief, perhaps knowing that his learned brothers (there were a few learned sisters at the time) in private practice, mostly Asians then, would hardly be interested in handling cases of the likes of Ahmed Kondo. Ahmed Kondo’s case was simple. They were peasants in a village in Morogoro Region. During off-season, they were employed by the Regional Water Engineer to lay pipes. After four months, their services were terminated without any benefits. Ahmed Kondo felt it was unjust. His complaint to the labour officer bore no fruit. Ahmed Kondo and his folk filed a case in the Magistrate’s Court. They failed. Kondo did not give up. His was a fight for justice. He travelled to Dar es Salaam to complain to the Chief Justice. The Chief Justice discovered that the whole case was a nullity. It had been filed in the wrong court against the wrong party. It ought to have been filed in the High Court against the Attorney General. He set aside the judgment and extended time for filing a plaint in the proper forum. I drafted my first plaint. I asked Mzee Ahmed Kondo to procure the signatures of all the plaintiffs. I could have filed a representative suit but that would have taken time, and I did not want to make any technical slips. Mzee Kondo travelled by bus and by foot. He even obtained a permit from the relevant authorities to enter quarantined areas. After two weeks, he came back with a rumpled plaint. I filed it in court. The next hurdle was to bring witnesses to Dar es Salaam. Kondo and his fellow workers had no money. I requested and was granted the application for the case to be heard during criminal sessions in Morogoro by a sessions judge. I travelled to Morogoro by bus, and stayed with my dear comrade George Hadjivyanis who cycled me every morning to the court in my black gown. The hearing was held in an old colonial building with large open windows to allow the hoi polloi to witness the proceedings. Impressed by Mzee Kondo’s militancy, I put him in the dock as my star witness. I let him tell his story. He embarked on a long narrative, leaving no stone unturned except when interrupted by the judge to be relevant. Then came the real spectacle—cross-examination. The state attorney was one of my good students in labour law. He harangued the witness, trying to show that the witness was a liar. Ahmed Kondo, a liar! It enraged me but what could I do? Court etiquette required I stay mum and let the ‘majesty’ of law take its course. We lost the case. I was disheartened, but not so Mzee Kondo. On appeal, we won. The Court of Appeal agreed with us that the plaintiffs had been employed as monthly workers and not casual labourers. Therefore, they were entitled to a month’s wages in lieu of notice of termination. The judgment came five years after termination and three court cases, one of which was aborted. I was to meet Mzee Ahmed Kondo again after ten years. As the chairman of the Presidential Commission of Inquiry into Land Matters, I visited his village.7 I saw him raising his hand to speak. The district officer moderating the meeting ignored him. I noticed him. I allowed him to speak. Mzee Kondo had not mellowed with time. He railed against village and district leadership, accusing them of ‘grabbing’ peasant lands. Ahmed Kondo was my first case. In the twilight of the nationalist period, I handled two legal briefs. I was then the chairperson of the Legal Aid Committee. Transition The two cases I did on the cusp of the transition from nationalism to neoliberalism were transformative for me, at a political and personal level. The cases pushed me beyond the vulgar idea of law as just superstructure, towards a more nuanced understanding: that law is deeply implicated in the very basis of productive relations, and that law does matter. More important for me was the realisation that, at certain moments, law can become a site of struggle for the working people (Shivji 2021c). Let me then turn to the cases. Mama Martha Wejja was a typist at Radio Tanzania, a public broadcasting station. Earning TZS 530 gross per month (about USD 65 then), she had to support her children singlehandedly since her husband was bedridden. Encouraged by the women’s wing of the ruling party, she stood for elections in the Ilala constituency in the 1980 general elections. The other candidate, also nominated by the party under the single-party system, was Kitwana Kondo. Kondo was a formidable opponent. He had money and connections. He had been the incumbent of the Ilala seat for three consecutive terms. Wejja lost the election. She sought legal aid from the Legal Aid Committee. With my colleague Professor Gamaliel Fimbo, I undertook to advocate for Mama Wejja. Our main grounds were that Kondo used tribalism, sexism and differing education qualifications to sway the voters. Each side fielded close to twenty-five witnesses. Wejja’s witnesses, with a few exceptions, were mostly working people. Kondo’s were mostly top-notch party and government functionaries. The trial lasted three gruelling months. Each day, the public gallery was full. There was enormous public interest in the contest between David(a) and Goliath. The trial threw up some memorable moments with their own tale to tell. Murtaza Lakha, a leading lawyer in the country, was defending Kondo. His line of cross-examination was calculated to attack Mama Wejja’s character and credibility. He asked her about her family life, her husband and number of children. He began to direct his questioning to show that she had abandoned her sick husband, that a supporter of hers was her boyfriend and that her husband had not fathered some of her children. My tolerance snapped. I was on my feet to object. The judge simply muttered under his chin, telling Lakha to ‘Spare her that … ’! The sexist line of cross-examination was not rare. It was frequently used in cross-examining Wejja’s female witnesses. There was little I could do. I had to swallow my anger. Despite the humiliation that lawyers in court often subject ordinary people to, one cannot help but admire their persistence and patience in the fight for human dignity. For example, there was this exchange between Wejja and the defence counsel Lakha. Lakha: You have dared to come to this court and tell lies because you have been given a free lawyer. Wejja: And you dare to tell that lie because you have been paid to do so. One of our important witnesses was a police officer who had been in charge of security during campaign meetings. In the dock, he turned against us. Little doubt that he had been tampered with. With droplets of sweat on his forehead, my co-counsel bent down to ask: ‘Shall I have him declared hostile?’ I said: ‘No, just wind up the examination’. The defence counsel had a field day. He led the witness through the narrative as if he was a defence witness. In his judgment, the judge also made ample use of his testimony to corroborate defence witnesses. Reading the judgment before a packed court, Justice Dan Mapigano dismissed the petition, finding the petitioner’s witnesses lacking in credibility.8 The judgment did not go down well with the public. Outside the court I heard a commotion. A fracas broke out between Mama Wejja and Kondo’s lady friend. A policeman had to whisk me out of the court through the judge’s door. Back on campus, my young comrades in the committee vehemently argued that we should appeal. My co-counsel was not interested. He told me point blank that he had spent enough time on the case. He had his children to take care of. He was telling me that charity began at home. Disheartened, I passed on the message to the committee. My comrades were adamant. They promised to prepare all the necessary papers and stand by me through the appeal process. In the event, we won the appeal. Even before the judges had left the court, there was a big applause. I was carried shoulder high by admirers. Mama Wejja was not present to witness her victory. She had been advised to stay home for security reasons (Ngaiza 1982). The Wejja case earned the Legal Aid Committee of the University of Dar es Salaam great respect and credibility. For me personally, it was a bitter-sweet victory. Was I lending legitimacy to the bourgeois legal ideology of equality and justice which, as an academic, I had relentlessly critiqued? The second case during the transition was of a different genre, more to my liking than the first. Here was a case of the working class about whom I had been writing since my student days. My doctoral thesis was on ‘Law, State and the Working Class in Tanzania’ (Shivji 1986). In 1982, 300 workers of TAZARA (Tanzania-Zambia Railway), which was built by the Chinese, were declared redundant. They were among those who had been employed in the construction of the railway. They were skilled workers trained by the Chinese as technicians, locomotive drivers, station masters, mechanics, etc. Receiving no support from the state trade union, the workers turned to the Legal Aid Committee. We took up their case and filed the necessary papers in the case of Hamisi Ally Ruhondo & 115 Others v TAZARA. After a long gruelling trial before the Permanent Labour Tribunal (now the Industrial Court), we won the case. The court ordered reinstatement.9 The employer successfully appealed to the High Court. Undaunted, the workers briefed me to appeal. On appeal, we won. Using a little-known subsection of the Security of Employment Act of 1964, we argued that prior to the decision on redundancy there should have been meaningful consultation with the affected workers. The court accepted our position. Hamisi Ally Ruhondo became a celebrated precedent often cited in subsequent cases on redundancy during the privatisation period.10 The General Manager of TAZARA, a former army general from Zambia, refused to reinstate the workers. The only way I could enforce the court order was through criminal prosecution for disobedience of a lawful order. I could not execute the order against TAZARA because TAZARA was statutorily protected from the execution process. After obtaining permission of the Magistrate’s Court, the General Manager was charged. While the criminal proceedings were still on, the Zambian government recalled its appointee to save embarrassment. The trial continued in absentia, eventually resulting in conviction. On sentencing, I submitted that the relevant section provided for imprisonment of two years. ‘But the workers have asked me not to ask for a custodial sentence. … The workers, in their traditional mercy have asked me to ask the Hon. Court to use its powers under s.38 of the Penal code to make an order for conditional discharge’.11 The court agreed. It sentenced the accused to absolute discharge. A conditional discharge would serve no purpose, the magistrate said, ‘as the accused is out in a foreign country, being a citizen of that country’.12 The neoliberal moment The neoliberal mantra rested on three pillars: liberalisation of trade and finance; privatisation of public enterprises; and marketisation of social goods and services. Under structural adjustment programmes (SAPs) imposed on debt-ridden African countries by the international financial institutions (IFIs), the government was required to cut subsidies, balance budgets, withdraw from the economy and adopt austerity measures. The first generation of SAP conditions caused havoc in our societies, increasing poverty, infant mortality, illiteracy and malnourishment, as social services, which previously had been subsidised, now had to be paid for. The second-generation SAP conditions focused on so-called good governance—that is, competitive politics through the multiparty system, human rights and NGOisation of civil society. After the fall of the Berlin Wall and the unravelling of the Soviet Union, Nyerere read the signs on the wall. He spearheaded the move from a single-party to multiparty system. Taking advantage of the liberalisation of politics, a group of women led by Professor Anna Tibaijuka, a university lecturer, formed an independent women’s organisation. Baraza la Wanawake wa Tanzania (BAWATA) was registered under the Societies Ordinance, the old colonial law giving the registrar of societies unrestrained powers to control, direct and oversee registered societies and, if need be, deregister them at will. BAWATA’s relative independence from the establishment and its ability to raise funds did not go down well with the powers-that-be. Government functionaries openly and covertly tried to frustrate the functioning of BAWATA by issuing threats, requiring it to change its constitution on spurious grounds, and so on. I was engaged by BAWATA to help them navigate a mass of registrar’s directives and instructions.13 Ultimately, BAWATA’s registration was cancelled. I filed a constitutional petition challenging the constitutionality of some provisions of the Societies Ordinance. Pending the hearing and determination of the case, I managed to get an injunction restraining the registrar from cancelling BAWATA and striking it off the register. The BAWATA case truly turned out to be a long saga, lasting twelve years. The proceedings were replete with preliminary objections and appeals to the Court of Appeal. We succeeded in most of those appeals. The Chief Judge took time to constitute the three-judge panel to hear the case. Again, after the case was heard, there was inordinate delay in writing and delivering the judgment. The judgment was finally delivered, upholding the petition and declaring a number of the provisions of the Societies Ordinance unconstitutional, while awarding the petitioners TZS 20 million in general damages.14 The Attorney General’s office immediately filed a Notice of Appeal. That was fifteen years ago. Since then, I have not been appraised of any movement. Meanwhile, the leadership of BAWATA has dispersed. Some of them have passed on. Their chairperson, an unrepentant fighter for women’s rights, has occupied high positions in the UN structure and in Tanzania’s government. She has now turned her attention to other worthy causes, like the education of girls. The BAWATA case primarily involved freedom of association–right to organise—which was and is dear to my heart. In my 1989 monograph The Concept of Human Rights in Africa (Shivji 1989, 2023), I had argued that in the current historical and political conjuncture the right of people to self-determination and the right to organise occupied centre stage. Around these two rights, I suggested, working people could organise their resistance to imperialism on the one hand, and the local comprador bourgeoisie, on the other. My involvement in the BAWATA case, therefore, was not perchance but a conscious political action on the legal plane to practise what I had preached. The second case I worked on during the neoliberal moment had all the hallmarks of World Bank-imposed privatisation of public enterprises. The case involved the employees of the National Bank of Commerce (NBC). NBC was established following the nationalisation of private banks in 1967 under the Arusha Declaration. By 1997, the bank had some 130 branches all over the country, employing over 3,000 workers. Mkapa, a privatisation crusader, became president in 1995. Immediately he set out to privatise the bank under the tutelage of the World Bank. The World Bank argued that NBC needed restructuring because it was too huge and unwieldy. How big was NBC compared to the Standard Charter Bank, Nyerere quipped (Shivji et al 2020: 398–399). By this time Nyerere’s opinions mattered little. So, in 1997 the bank was broken into three banks—a microfinance bank, an NBC holding company and NBC (1997) Limited. Restructuring was simply a euphemism for privatisation. The divestiture of NBC (1997) Limited was one of the conditions set for Tanzania to qualify for the release of the tranche set aside for restructuring the financial sector.15 As the process of selling off majority shares of NBC gathered speed, employees became apprehensive. They saw redundancy coming. Their militant trade union—the Tanzania Union of Industrial and Commercial Workers (TUICO)—retained me. The workers’ main demands were: one, that there should be meaningful consultation before the decision on redundancy; two, that their collective agreement be observed; and, three, that they be paid their redundancy package before the new owner took over so that they could decide whether or not to continue with the new owner. I filed a judicial review application in the High Court, applying for orders of mandamus and prohibition, in effect orders to command the bank not to privatise before the process of redundancy consultation and payment of redundancy package had been completed. Pending hearing of the application, I successfully applied for a temporary injunction to restrain the divestiture process. That touched a raw nerve. The potential buyer had already been identified. It was ABSA Bank of South Africa. Mkapa wanted the process of privatisation speeded up to silence the critics with a fait accompli. The next five months saw an intense legal battle with numerous applications, preliminary objections, affidavits, counter-affidavits and court orders, some of them in favour, others against us. Eventually, denied leave to apply for judicial review and without the protection of a temporary injunction pending appeal, I moved post-haste to the Court of Appeal.16 Two remarkable trade unionists, Jane Joseph (Generose) and Alquin Senga, helped me maintain my sanity during this trying period. The case was not without some hilarious moments. Strangely, the potential buyer—ABSA—was given a management contract to manage NBC pending signature of the memorandum of the sale of shares. The General Manager and the Human Resources Manager were white South Africans. The Human Resources Manager was an expert, I was told, in Bantu psychology! During the course of the case, I was told by the bank’s Tanzanian lawyer that the Bantu specialist wanted to see me, presumably to assess this Bantu who was putting up robust resistance! Of course, I declined. I was not a museum piece, I quipped. Ultimately, the case ended up in the Court of Appeal. The judge hearing the application was one of our sober first-generation judges. After hearing my submissions, he told the counsel off record that he was inclined to grant the application but knew that the government in all probability would not honour the court’s decision. Rather than bring the judicial process into disrepute, why could we not settle the matter out of court, he advised. I jumped at the opportunity, intimating that I was happy to settle the case out of court. I knew time was on my side. The case was adjourned. I met senior state attorneys in the Attorney General’s chambers. We reached a settlement, which included making the collective agreement part of the court order and, therefore, embodied in the court decree. Finally, I make a brief mention of one important constitutional case I handled because it relates to another of my pet issues, the question of the union between Tanganyika and Zanzibar. The Union The underbelly of the Tanzanian constitutional order is the question of the Union. We have a quasifederal, two-government association in which the Zanzibar Government has semi-autonomous status. The Union government’s jurisdiction extends to Union matters in both parts of the Union. The Union government also takes care of all matters of Tanzania’s mainland. Following the great 1983–84 constitutional debate, I argued in the Eastern Africa Law Review that the underlying tensions and contradictions of the Union could not be resolved through constitutional tinkering (Shivji 1983: 23–25). The Union question was pre-eminently a question of democracy and the right of nations to self-determination. I had further argued that the Union could not be imposed and that the final arbiters were the people of Zanzibar. Finally, various issues raised in relation to the Union and its structure could be decided upon only by a referendum among the Zanzibaris. As fate would have it, the popular referendum that I had theoretically advocated five years earlier landed in my lap in a practical way. Sometime in 1989, Seif Shariff Hamad, a popular Zanzibari politician with a solid base in Pemba, was charged with a number of criminal offences and remanded in custody. Hamad was a prominent member of the ruling party, the CCM. In 1984, he became Chief Minister after the previous president, Aboud Jumbe, was forced to resign for advocating a three-government federal structure. In 1985, Hamad contested nomination for Zanzibar’s presidency within the party but lost it by a narrow margin. Although he was again appointed Chief Minister under the new president, his followers were disgruntled. In 1988, Hamad and some of his followers were expelled from the party for, allegedly, plotting against the incumbent president. Outside the party and the government, Hamad propagated a referendum to decide whether the people of Zanzibar wanted the Union. Hamad outside was perceived to be a greater danger than when he was inside (Shivji 2008). Harassment followed. Eventually, he was charged for illegal assembly and retaining government security documents contrary to the National Security Act of 1970. I was approached to represent Hamad. The Legal Aid Committee, then under the chairmanship of my colleague and close friend, Wilibert Kapinga, granted Hamad and his co-accused legal aid on the grounds of public interest. Together with another colleague, I appeared for Hamad in the Magistrate’s Court in Zanzibar. After several applications for bail, which were invariably denied, I gave public notice to the court that I would apply for the case to be removed to the High Court. I wished to raise a constitutional issue on the validity of the charge on the grounds that the law under which Hamad had been charged was not applicable to Zanzibar. The National Security Act of 1970 had not been tabled before the House of Representatives, contrary to Zanzibar’s Constitution. The next day, the newspapers were awash with headlines. My submission had hit a raw nerve in the body politic. Government machinery went into motion. Irresistible pressure was brought to bear on the chairman of the Legal Aid Committee. Behind my back, the chairman wrote a letter to the High Court of Zanzibar, withdrawing legal aid. No reasons were given (Peter 1997: 659–661). I had already filed a habeas corpus application. On the hearing date, I applied to withdraw. I had no leg to stand on. The application was granted. I assisted the private counsel who took over from me to argue the habeas corpus application. It did not succeed.17 Hamad remained in custody. Hamad’s case was a clear instance of the state waging lawfare against its opponent. The state lawfare was waged not only in courts but also in remand custody, where Hamad was denied various benefits such as the right of access to his lawyers and the right of his relatives to visit him. He was even denied a mosquito net! Lawfare becomes warfare Lawfare becoming warfare was not uncommon in Zanzibar, particularly during general elections. In the aftermath of the general elections in 2000, to give one example, police fired live ammunition on thousands of demonstrators in Pemba. Between forty and sixty people were killed. Hundreds were injured. Women complained of rape and other forms of gender violence. More than 200 people sought refuge in Mombasa. For the first time in Tanzania’s history, the country known to be a safe haven for refugees from surrounding countries itself created refugees.18 Worse violence was yet to come—this time around, not in Zanzibar but on the Tanzania mainland. In scale and brutality, the killing of protestors during the October 2025 general elections on the mainland surpassed the electoral violence historically associated with Zanzibar. The Commission of Inquiry under the former Chief Justice Mohamed Othman Chande estimated total deaths to be more than 518.19 By all accounts, this is a gross underestimate. There is little doubt that the death toll ran into thousands. Both the Commission and other accounts cite examples of people who had nothing to do with the protest being fired at and killed.20 On 31 October, 13 people who were watching TV at a kiosk were fired at by the police. A few escaped, others died. A mother with a child on her back was drawing water from a well when she heard bomb sounds. She ran. Her child fell down after being shot in the head. A young man of 35 sitting near his shop was shot four times. According to his mother, her son was shot in the arm. He fell down. The police followed him and shot three more bullets in his back breaking two of his spinal bones. Another bullet landed at the base of his heart. It remains lodged there to this day. Those who were injured numbered 2,380; almost half were injured by gun shots; 9.2 per cent suffered serious injuries. The protestors did not carry guns. The police did. Yet the worthy Chande Commission did not recommend that the police who fired shots and the officers who ordered the shooting should be held criminally liable. In the pre-election period, there was a spate of abductions and forced disappearances. Police reported to the Commission that, between 2023 and 2025, 758 persons disappeared or were abducted. Out of these, 513 were found. Eight cases were under investigation. 245 people were still missing. Police gave spurious reasons like unrequited love, indebtedness, self-inflicted disappearances, feigned abductions and so on for the missing people. This, in the face of the popular perception, based on eye-witness accounts and surrounding circumstances, that the police were allegedly responsible for abductions and disappearances. Activist lawyers filed habeas corpus applications in cases of abductions and disappearances. The police simply informed the judges that they were not holding the subject and did not know his or her whereabouts. Judges acquiesced without further ado. In my view, the judiciary did not acquit itself well, to say the least. Insurgent lawfare has little space when the coercive apparatus of the state turns to warfare with impunity. The liberal model of separation of power, rule of law and independent judiciary falls apart. People lose faith. Ruling power loses legitimacy. Crisis becomes a catastrophe. Society demands accountability for the wounds and trauma it has suffered. The powers-that-be try to bandage the wounds, ignoring the trauma. Establishment priests and sheikhs preach tolerance and pray for healing. Official and popular narratives diverge. Hegemony declines precipitously and we, the intellectuals, are left groping in the dark looking for a silver lining.